FRI0002 Inhibition of chemokine receptors ccr1 and ccr6 as promising therapies for rheumatoid arthritis. (23rd January 2014) - Jaen, J. C.; Dairaghi, D.; Leleti, M.; Powers, J. P.; Wang, Y.; Zhang, P.; Schall, T. J.
Abstract : Background: Chemokines are key regulators of leukocyte activation and recruitment to sites of inflammation. Of particular relevance in rheumatoid arthritis (RA), the chemokine receptors CCR1 and CCR6 are thought to drive monocyte/macrophage and Th17 cell recruitment, respectively, into RA joints. We recently demonstrated the clinical benefit of our first-generation CCR1 antagonist (CCX354) in a Phase 2 trial in RA patients (Tak et al., 2012). To date, no therapeutic agents targeting CCR6 have progressed into clinical evaluation. Objectives: To identify orally active small molecules that selectively target either CCR1 or CCR6 and possess overall profiles suitable for clinical development. Key selection criteria include their potency on CCR1 or CCR6-expressing primary human cells, their selectivity, and their ability to prevent chemotaxis of freshly isolated human blood leukocytes towards RA synovial fluid samples. Methods: The in vitro potency of CCX486 (CCR1 antagonist) was assessed by inhibition of CCL15-mediated chemotaxis of THP-1 cells and human blood monocytes. The in vitro potency of C0339589 (CCR6 antagonist) was assessed by inhibition of CCL20-mediated chemotaxis and binding using a human NK cell line and CCR6 + enriched human PBMC. CCX486 and C0339589 were assessed for their ability to block the CCR1 and CCR6-mediated chemotaxis, respectively, of human blood leukocytes towards RA synovial fluids. Results: CCX486 potently blocks CCL15-mediated chemotaxis with an IC50 of 0.61 nM (THP-1 cells). In 100% human serum, CCX486 blocks CCL15-mediated chemotaxis with an IC50 of 1.0 nM (THP-1 cells) and 1.8 nM (human monocytes). CCX486 also completely blocks the monocyte-chemotactic activity displayed by human RA synovial fluid samples. C0339589 potently blocks CCL20-mediated chemotaxis of CCR6 + enriched human PBMC (IC50 : 38 nM). C0339589 also blocks the lymphocyte-chemotactic activity displayed by human RA synovial fluid samples (IC50 10-30 nM). Both CCX486 and C0339589 are highly selective for CCR1 and CCR6, respectively, when tested against a wide screen of chemokine and chemoattractant receptors. Conclusions: CCR1 : A second-generation CCR1 antagonist (CCX486) was designed de novo using existing knowledge from several other CCR1 programs that have previously advanced into clinical evaluation. This compound, which shares very little structural similarity to first-generation molecule CCX354, is nevertheless equally selective for CCR1 and orally bioavailable in preclinical species (Dairaghi et al., 2011). CCX486 is about 20 times more potent on human CCR1 than CCX354. CCX486 was shown to block CCR1-mediated chemotaxis of human blood monocytes towards RA synovial fluid samples. CCR6 : Several chemical lead series were identified using a proprietary high-throughput screening format. Optimization of one of these series resulted in advanced molecules such as C0339589. This molecule is highly potent on human and mouse CCR6 and displays properties conducive to its use for the treatment of diseases such as RA, psoriasis and multiple sclerosis. References: (a) Dairaghi, D. et al. (2011) Clin. Pharmacol. Ther., 89(5), 726; (b) Tak, P.P. et al. (2012) Ann. Rheum. Dis., online May 15, 2012. Disclosure of Interest: J. Jaen Shareholder of: ChemoCentryx, Employee of: ChemoCentryx, D. Dairaghi Shareholder of: ChemoCentryx, Employee of: ChemoCentryx, M. Leleti Shareholder of: ChemoCentryx, Employee of: ChemoCentryx, J. Powers Shareholder of: ChemoCentryx, Employee of: ChemoCentryx, Y. Wang Shareholder of: ChemoCentryx, Employee of: ChemoCentryx, P. Zhang Shareholder of: ChemoCentryx, Employee of: ChemoCentryx, T. Schall Shareholder of: ChemoCentryx, Employee of: ChemoCentryx